Nursing Human Resource Practices and Hospitals' Performance Excellence: The Mediating Role of Nurses' Performance - Zoromba, Mohamed A.; El-Gazar, Heba E. (Acta Biomedica Atenei Parmensis, 2021)
Background: There is increasing need to achieve performance excellence in healthcare organizations. Nursing human resource practices (HRP) and nursing performance are important variables to achieve it. Aim: To investigate the effect of nurses’ perceptions of HRP on achieving hospitals' performance excellence through the mediating role of nurses' job performance. Methods: The study used a cross-sectional research design and recruited 329 nurses from 16 hospitals. Three self-reported questionnaires were used; HRP scale, Baldrige dimension scale and six-dimension scale of nursing performance (6-D). Results: Nurses' perceptions of HRP, hospitals' performance excellence and nurses' job performance were all significantly correlated (p < 0.01). Nurses' job performance was found to play a mediating role in the association of nurses' perceptions of HRP and hospitals' performance excellence. Conclusion: Nurses’ perceptions of HRP can help hospitals achieve performance excellence by improving nurses' job performance. Clinical Relevance for nursing management: Particular attention should be paid to improve nursing HRP and nursing performance.